Doping in sport: Misuse, analytical tests, and legal aspects - Cowan, D. A.; Kicman, A. T. (Clinical Chemistry, 1997)
As part of the International Congress of Clinical Chemistry, a symposium, Doping in Sport: Misuse, Analytical Tests, and Legal Aspects, was held, a week before the start of the Olympic Games at Atlanta, bringing together a number of international experts concerned with various aspects of controlling drug abuse in sport. The presentations focused particularly on anabolic-androgenic steroids (AAS), these analytes still comprising the greatest number of positive findings in samples tested by International Olympic Committee (IOC)-accredited sports drug-testing laboratories. Although various aspects of AAS use and detection have been reported on in the last decade, the proceedings of this symposium, published in this issue of Clinical Chemistry, bring together health, social, endocrine, and analytical perspectives in a widely read peer-reviewed journal.